Key determinants of foreign direct investment in the ASEAN Region - Shafai, Nor Anis; Firdaus, Nurul Iffah; Shekh Zain, Rozihanim; Ahmad, Zulaiha; Yusof , Abdul Hafiz (International Journal of Accounting, Finance and Business, 2024)
Foreign direct investment (FDI) refers to money invested by international organizations and individuals in host countries to gain control of businesses and earn profits. This study aims to understand the determinants of FDI in the ASEAN region and their impact on FDI inflows in the 10 ASEAN countries over a 10-year period (2011-2021). The dependent variable in this study is FDI net inflows, while the independent variables are gross domestic product (GDP), inflation, labour force, and trade openness. The findings indicate that both the labour force and trade openness have a significantly positive impact on FDI in ASEAN countries, suggesting that greater trade openness attracts higher levels of FDI. Conversely, GDP and inflation are negatively associated with FDI inflows, with inflation being statistically significant and the labour force showing no significant impact on FDI. These results highlight the importance of trade openness and economic stability in attracting FDI. This study provides valuable insights for policymakers to improve and monitor regulations affecting FDI inflows, ultimately fostering a more favourable investment climate in the ASEAN region.